Optimal capacitor placement in radial distribution system for loss minimization using particle swarm optimization - Ismail, Abdiwahab Mohamed (Brac University, 2024)
This final year design project is submitted in partial fulfilment of the requirements for the degree of Master of Science in Electrical and Electronic Engineering, 2022.